Dick Tracy. Volume 1 - Segura, Alex, 1980-; Moreci, Michael (Dick Tracy., 2024)
In the aftermath of World War II, the country stands frozen, waiting for the other shoe to drop. In The City, a brutal murder draws the attention of rising star detective Dick Tracy, who soon discovers the bloodshed is just the beginning of a complicated web that threatens to ensnare everything he cares about. - Amazon